328. Universal PCR Testing- Is It Worth It?. (15th December 2022) - Birk, Navina K; Saikia, Kasturi; Ramesh, Mayur; Samuel, Linoj; Tibbetts, Robert
Abstract: Background: Universal PCR and Next Generation Sequencing (uPCR/NGS) is a major advancement in microbiology. It is a highly sensitive and specific test that amplifies ribosomal RNA in samples to detect bacterial and fungal pathogens. We investigated the uPCR/NGS tests sent from Henry Ford Health (HFH) and the effect obtaining this test had on patient care. Methods: We completed a retrospective, observational study assessing all consecutive uPCR/NGS tests obtained from at HFH from 2016-2021. This included uPCR/NGS for detection of bacterial, fungal, mycobacterium tuberculosis (MTB), and non-tuberculosis mycobacterium (NTM). All samples were of non-blood fluids and tissue samples. Patients concurrent tissue cultures and blood cultures from day of uPCR/NGS, and within 6 months of obtaining the uPCR/NGS sample were evaluated. Primary outcomes included if uPCR/NGS testing resulted in a change of choice or duration of antibiotic therapy. Results: At HFH, 226 uPCR/NGS tests from 111 samples were analyzed. This included 83 bacterial, 51 MTB, 51 NTM, and 41 fungal uPCR/NGS tests. Of the 226 uPCR/NGS tests, 31 tests (13.7%) resulted with positive result on uPCR/NGS. A total of 31 tests (13.7%) were ordered on a known culture positive sample, and 195 (86.3%) were ordered on a culture negative sample. Of samples sent from a culture positive sample, 7 (22.6%) resulted with positive uPCR/NGS results. 3 (42.9%) matched the tissue cultures, and 2 (28.6%) matched the patients' blood cultures. None of the patients had any change in choice or duration of antibiotics based on uPCR/NGS results. Of the samples sent from a culture negative sample, 24 (12.3%) samples resulted with positive uPCR/NGS results. 2 (8.3%) matched a patient's tissue cultures and none matched blood cultures. Change in antibiotic choice or duration occurred in 16 (17.6%) patients. The samples with the highest rates of change in management included cerebrospinal fluid (42.9%), brain tissue (36.4%), cardiac valvular tissue (27.3%), lymph nodes (25%), synovial fluid (20%). Figure 1: Flowchart of Results and Impact on Management Conclusion: Our results show that uPCR/NGS has an overall low percent of impact in clinical outcomes, but it is a useful test in when used on a culture negative sample in certain sample types, along with a high index of suspicion for infection. Disclosures: All Authors : No reported disclosures.